2022
DOI: 10.3390/plants11243536
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Shell and Nut Yield Components after Ca, Mg and K Preharvest Spraying on Hazelnut Plantations in Southern Chile

Abstract: To determine the effects of pre-harvest calcium (Ca), magnesium (Mg) and potassium (K) spraying on the antioxidant activity and capacity of hazelnut (Corylus avellana L.) shells, as an approach to sustain the utilization of the main residue derived from this industry, four commercial hazelnut (Tonda di Giffoni) orchards located in Southern Chile (Cunco, Gorbea, Perquenco and Radal), during the 2018/19 season were sprayed three times with five combinations of Ca (300 and 600 mg L−1), Mg (300 and 600 mg L−1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Chile has become the main producer country from the Southern Hemisphere, with an off-season nut supply of approximately 52,100 t (4.73% of total world production) in the 2021/2022 season [18] and an estimated production of 136,000 t year −1 for 2030 [18,19]. This nutshell has a mass value of over 50% of the total fruit weight (w/w) in stabilized nut [9,20]. It is becoming the main hazelnut byproduct production.…”
Section: Productive Context and Expectative Of Hazelnut And Walnut Sh...mentioning
confidence: 99%
See 4 more Smart Citations
“…Chile has become the main producer country from the Southern Hemisphere, with an off-season nut supply of approximately 52,100 t (4.73% of total world production) in the 2021/2022 season [18] and an estimated production of 136,000 t year −1 for 2030 [18,19]. This nutshell has a mass value of over 50% of the total fruit weight (w/w) in stabilized nut [9,20]. It is becoming the main hazelnut byproduct production.…”
Section: Productive Context and Expectative Of Hazelnut And Walnut Sh...mentioning
confidence: 99%
“…Regarding the hazelnut antioxidant features, Manterola-Barroso et al [9] reported a mean ORAC antioxidant capacity (AC) of 2119 µmol TE g −1 DW in control treatments of TDG shell samples, demonstrating the interesting antioxidant potential of hazelnut shells. Moreover, Pelvan et al [32] have reported AC (ORAC method) values from roasted hazelnut skin samples, which could be a part of and an approach to the antioxidant capacity of the hazelnut shell of approximately 1219 µmol TE g −1 , also TPC content (Folin-Ciocalteu) of 72.25 mg GAE g −1 and RSA (DPPH method) of 1.01 mg mL −1 (extract).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
See 3 more Smart Citations